Inventorying of herbal remedies used to control small ruminant’s parasites in Southern Benin - Attindéhou, Sabbas; Houngnimassoun, Marcel Aristide; Salifou, Sahidou; Biaou, Cyprien Félix (International Multidisciplinary Research Journal, 2012)
A botanical survey was undertaken in two agro-ecological zones of southern Benin, aiming inventorying the plants used by farmers as antiparasitic remedies in small ruminants. In total, 253 smallholders of livestock have been sampled throughout 90 villages and underwent a structured interview. The result revealed that 20% of interviewed people use indigenous knowledge based on plants. Twenty two plants of 18 families have been cited as effective remedies to parasitic diseases of small ruminants. Xanthoxylum zanthoxyloides (Rutaceae) and Carica papaya (Caricaceae) were the most frequently cited(75% of plants users) followed by Spondias mombin (Anacardiaceae) and Moringa oleifera (Moringaceae). Leaves were the most frequently plant organ generally used in infusion (100%). Farmers think this medication is effective. Though widely reported, the effectiveness of these recipes still belongs to empirical knowledge awaiting proof.